Pre-service Teachers' Metaphorical Perceptions towards the Concept of Scientist - (:unkn) unknown (KAMLA-RAJ ENTERPRISES, 2015)
The purpose of this study is to display pre-service teachers' perceptions towards the concept of scientist through metaphors. Phenomenology, which is one of the qualitative research designs, was used in the study. Data was collected from 154 pre-service teachers studying in different departments of Ataturk Faculty of Education' at Marmara University in Turkey, in the spring semester of 2013-2014 academic year. They were asked to complete the sentence Scientist is like ..; because... The collected data was analyzed through content analysis technique and interpreted accordingly. The findings indicated that 87 different metaphors were generated by the pre-service teachers for the concept of scientist. These metaphors were then categorized by considering their common features and 16 categories and 8 themes were obtained. It was concluded that pre-service teachers had positive perceptions towards scientist while two negative metaphors were found among the metaphors that pre-service teachers generated for the concept of scientist.
Keywords: Culture and Education; Metaphor; Scientist; Pre-service Teacher; Education; STUDENTS; SCIENCE; KNOWLEDGE; IMAGES